Hubungan Kecanduan Game Online dengan Motivasi Belajar Siswa Kelas XI SMK Negeri 3 Mukomuko - Putri, Sucie Alenta; Fitria, Linda; Yunus, Yuliawati (YASIN, 2024)
This This research aims to determine the relationship between online game addiction and the learning motivation of class XI students at SMK Negeri 3 Mukomuko. The method used in this research is descriptive quantitative correlational. The population in this study was 127 people. The sampling technique used was stratified random sampling, resulting in a total sample of 96 people. Based on the instrument used in data collection in this research, it is a questionnaire prepared according to the Likert scale model. Data analysis was carried out using SPSS and Microsoft Excel. Based on the research results, the rcount value is 0.837 > rtable 0.198, it can be concluded that there is a significant connection between online game addiction and the learning motivation of class XI students at SMK Negeri 3 Mukomuko.